Research on the architecture of space-ground integrated information network: integration of communication, networking and computing - Zhigang YU; Xu FENG; Zhaoxiang HUANG; Zhou LU (Dianxin kexue)
With the continuous expansion of human activities from the terrestrial to the ocean and space, the countries all over the world have advanced the layout of space-ground integrated information network to provide seamless coverage and ubiquitous connection services.Space-ground integrated information network is the deep integration of space network and terrestrial network, not the expansion of terrestrial network to space environment.Starting from the perspective of integration, firstly the development status, existing problems and challenges of the internet, public land mobile network (PLMN), and space networks were sorted out.Secondly, the research status of the space-ground integrated information network architecture and the development trend of the new network architecture such as cloudification and intelligence was summarized.Thirdly, a communication-networking-computing integrated space-ground integrated information network architecture was proposed from different dimensions: physical architecture, functional architecture (including the integrated communication system, the integrated network system and the integrated information system), physical-functional architecture mapping problem.Finally, the network architecture optimization problem was modeled as a multi-objective optimization problem.It was expected to provide valuable suggestions and references for the research, construction and standardization of space-ground integrated information network.